Two sides of one medal: Arable weed vegetation of Europe in phytosociological data compared to agronomical weed surveys. Issue 1 (29th March 2022) - Bürger, Jana; Küzmič, Filip; Šilc, Urban; Jansen, Florian; Bergmeier, Erwin; Chytrý, Milan; Cirujeda, Alicia; Fogliatto, Silvia; Fried, Guillaume; Dostatny, Denise F.; Gerowitt, Bärbel; Glemnitz, Michael; et al.
Abstract: Questions: Two scientific disciplines, vegetation science and weed science, study arable weed vegetation, which has seen a strong diversity decrease in Europe over the last decades. We compared two collections of plot‐based vegetation records originating from these two disciplines. The aim was to check the suitability of the collections for joint analysis and for addressing research questions from the opposing domains. We asked: are these collections complementary? If so, how can they be used for joint analysis? Location: Europe. Methods: We compared 13 311 phytosociological relevés and 13 328 records from weed science, concerning both data collection properties and the recorded species richness. To deal with bias in the data, we also analysed different subsets (i.e., crops, geographical regions, organic vs conventional fields, center vs edge plots). Results: Records from vegetation science have an average species number of 19.0 ± 10.4. Metadata on survey methodology or agronomic practices are rare in this collection. Records from weed science have an average species number of 8.5 ± 6.4. They are accompanied by extensive methodological information. Vegetation science records and the weed science records taken at field edges or from organic fields have similar species numbers. The collections cover different parts of Europe but the results are consistent in six geographical subsets and the overall data set. The difference in species numbers may be caused by differences in methodology between the disciplines, i.e., plot positioning within fields, plot sizes, or survey timing. Conclusion: This comparison of arable weed data that were originally sampled with a different purpose represents a new effort in connecting research between vegetation scientists and weed scientists. Both collections show different aspects of weed vegetation, which means the joint use of the data is valuable as it can contribute to a more complete picture of weed species diversity in European arable landscapes. Abstract : Vegetation of arable weeds is sampled by two rarely interacting scientific communities: phytosociologists and weed scientists from an agronomical background. We compare two data collections. Agronomical weed surveys were taken mainly in field centres and have a lower species richness than phytosociological data, taken presumably mostly in field edges. Combined use is proposed for a more accurate picture of weed vegetation.